Malaysian Chef: the Development of a 2D Malaysian Food Mobile Game - Kot, Yuki; Mohd Farhan Md.Fudzee, (Applied Information Technology And Computer Science, 2024)
Malaysian has many unique aspects that identifies us as a country that has independently grown and thrive in this modern era. Amongst its diverse cultures, one aspect that unites all of Malaysian most passionately is our food, encompassing dominantly of Malay, Chinese and Indian flavours. However, the online gaming market lacks such local content, overshadowed by foreign offerings. Thus, a kids-friendly 2D mobile game, ‘Malaysian Chef’, is proposed. Operating on Android platform, it aims to educate users, especially primary school children, on the rich diversity of Malaysian dishes. By implementing an interactive food preparation gameplay, the game hopes to raise awareness and appreciation for the country’s culinary diversity amongst the dominating feature of foreign food in the online game market.